Beginning Information Cards and CardSpace - Mercuri, Marc (Apress, 2012)
The Internet was designed without identity in mind. The result is a patchwork of solutions that try to fill the gap, none of them ideal. With cases of identity theft and phishing rising exponentially, something needs to change. With widespread industry agreement on both the Laws of Identity and the concept of an identity metasystem, that change is upon us. With Microsoft’s Windows CardSpace being deployed with the .NET Framework 3.0 and installed by default with Windows Vista, the industry is poised for an “identity big bang.” As someone who works with technologies in the very early phases of development, as well as with customers looking to utilize these technologies, I can see that information cards and Windows CardSpace have the opportunity to truly transform the way that identity is handled on the Internet. There has been a number of great documents made available on the Web that delve into the subject with considerable depth. The challenge is that identity is typically not at the forefront of many technology books today, and going directly to those documents can be a bit daunting. This book is, as its name implies, for novices and professionals. It’s designed to provide an understanding of the concepts, an overview of the projects and technology landscape, and coverage of the technical implementation skills.